2014
DOI: 10.1155/2014/159790
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Behavior of Fiber Reinforced PP ECC Beams under Reverse Cyclic Loading

Abstract: When a structure is hit by earthquake, tremendous amount of seismic energy is released and structure is subjected to reverse loads. The mechanical properties of FRP reinforced PP ECC beams and coupon RC beam under reverse cyclic load controlled by displacement are investigated. Curing ages, reinforcement ratio, and volume fraction of PP fiber are parameters under survey. It is shown that multiple saturated cracking occurred in PP ECC beam and no crushing appeared. The PP ECC can enhance strength and energy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Standard mix of ECC (M45) comprising of cement, fly ash, polyvinyl alcohol (PVA) fiber, silica sand, water and superplasticizer. The use of polypropylene (PP) fiber in ECC is rather limited [9][10][11] despites of its lower cost and environmentally friendly. Compared to fly ash, the use of GGBS as SCM in ECC is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Standard mix of ECC (M45) comprising of cement, fly ash, polyvinyl alcohol (PVA) fiber, silica sand, water and superplasticizer. The use of polypropylene (PP) fiber in ECC is rather limited [9][10][11] despites of its lower cost and environmentally friendly. Compared to fly ash, the use of GGBS as SCM in ECC is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In typical ECC mixture, polyvinyl alcohol (PVA) fiber is the most common type of fiber used due to its excellent performance in tensile ductility and multiple cracking [1,6,[12][13] at a lower cost if compared to polyethylene (PE) fiber. The use of polypropylene (PP) fiber in ECC is rather limited [8,[14][15] despites of its lower cost and environmental friendly. In previous study [8], when 3.0% of PP fibers combined with fly ash, cement, sand and water, strain hardening behavior can be observed from the uniaxial test.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [21,26] found that PP-ECC was effective in replacing transverse reinforcements, providing sufficient shear strength, and dissipating more seismic energy. Yaw and Han [27] concluded that PP-ECC exhibited enhanced strength and energy dissipation capacity when subjected to reverse cyclic loading. The use of PP-ECC jacket at the plastic hinge region of the bridge column was beneficial to bearing greater plastic deformation and dissipating more seismic energy [28].…”
Section: Introductionmentioning
confidence: 99%